2008
DOI: 10.1007/s00223-008-9200-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adenylate Cyclase 10 (ADCY10) Polymorphisms and Bone Mineral Density in Healthy Adults

Abstract: Phenotypic variation in bone mineral density (BMD) among healthy adults is influenced by both genetic and environmental factors. Genetic sequence variations in the adenylate cyclase 10 (ADCY10) gene, which is also called soluble adenylate cyclase, have previously been reported to be associated with low spinal BMD in hypercalciuric patients. Since ADCY10 is located in the region linked to spinal BMD in our previous linkage analysis, we tested whether polymorphisms in this gene are also associated with normal BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In bone, increased [HCO 3 Ϫ ] inhibits osteoclast proliferation and differentiation through sAC, as demonstrated by siRNA knockdown of sAC (37). Expression of sAC may have consquences on bone health: a polymorphism in the adenylate cyclase 10 gene has been reported to "modestly" associate with bone mineral density (40).…”
Section: Discussionmentioning
confidence: 99%
“…In bone, increased [HCO 3 Ϫ ] inhibits osteoclast proliferation and differentiation through sAC, as demonstrated by siRNA knockdown of sAC (37). Expression of sAC may have consquences on bone health: a polymorphism in the adenylate cyclase 10 gene has been reported to "modestly" associate with bone mineral density (40).…”
Section: Discussionmentioning
confidence: 99%
“…The gene was subsequently identified as the soluble adenylate cyclase gene, and subsequent studies disclosed a direct relationship between the number of mutations found in this gene and the severity of the defect in bone formation [22]. Recently, Ichikawa et al [23] found a modest association between this soluble adenylate cyclase polymorphism and the spinal areal BMD in premenopausal women. It is unlikely that one specific genetic mutation or polymorphism will be responsible for bone loss in children with IH.…”
Section: Possible Mechanisms Contributing To Bone Loss In Pediatric Imentioning
confidence: 99%
“…Ϫ effect on bone volume fraction of cultured mouse calvaria was blocked by the sAC inhibitor. Reed et al (46) reported sAC was associated with low spinal BMD in hypercalciuric patients, and Ichikawa et al (47) found a modest association between sAC polymorphism and spinal areal BMD in premenopausal white women. Our findings are consistent with the above results, indicating that sAC expression is essential for bone formation and should be the early signaling event mediator in icariin-promoted bone formation.…”
Section: Primary Cilia Mediate Camp/pka/creb In Osteogenesismentioning
confidence: 99%